Performance of The Occupational Health, Safety, and Environment (HSE) Culture in Educational Laboratories - Deswati, Sri Ratih; Setyaningsih, Wahyu Adi (Jurnal Berkala Kesehatan, 2024)
The Department of Marine Science and Technology (MST) has a physics laboratory (dry and wet) and a field laboratory. Laboratory activities cannot be separated from potential hazards that can cause the risk of work accidents due to tools, materials, and the work environment. The establishment of a culture of health, safety, and the environment (HSE) and the application of a procedure for identifying possible risks and hazards, known as job safety analysis (JSA), are two strategies used to prevent and lessen work accidents in physics and field laboratories. Determining the efficacy of introducing HSE culture in the lab was the aim of this investigation. Analytical and observational cross-sectional methods were employed in quantitative research procedures. The variables used to evaluate whether the HSE culture has been applied are knowledge of HSE, the application of HSE, and comprehension of PPE. The results of observations showed that the application of HSE was reasonably efficient as a guide for safe and healthy activities; nevertheless, it still requires assistance and the fulfillment of many work processes in the laboratory.